A COMPARATIVE ANALYSIS OF ANTI-CORRUPTION INSTITUTIONS: THE CASE OF INDONESIA’S KPK AND SOUTH KOREA’S KICAC - Luca Santi; Martina Rossi; Giuseppe Lazzari (Cognitionis Civitatis et Politicae, 2025)
The establishment of independent anti-corruption agencies (ACAs) is a primary global strategy for combating systemic corruption. Indonesia’s Corruption Eradication Commission (KPK) and South Korea’s former Korea Independent Commission Against Corruption (KICAC) represent two prominent yet divergent models in Asia, both emerging from post-authoritarian transitions. Understanding their distinct institutional trajectories provides crucial insights into the dynamics of anti-corruption reform. This study conducts a comparative analysis of the institutional design, operational effectiveness, and political resilience of the KPK and KICAC to identify the determinant factors shaping their successes and challenges in fulfilling their mandates. A qualitative comparative case study approach was employed, analyzing foundational legal documents, official institutional reports, scholarly articles, and reputable media archives. The analysis focused on key variables including legal powers, degree of independence, resource allocation, and the prevailing socio-political contexts in which each agency operated. The findings indicate that the KPK’s comprehensive mandate, which includes investigative and prosecutorial powers, allowed for more high-profile enforcement actions compared to KICAC’s primary focus on prevention and policy coordination. However, this enforcement power also made the KPK a target of sustained political resistance, while KICAC faced challenges of relevance that eventually led to its institutional merger. The long-term success of an ACA depends not only on a robust legal mandate but, more critically, on sustained political support and strong institutional defenses against political co-optation. The divergent experiences of the KPK and KICAC offer vital lessons for designing and safeguarding effective anti-corruption institutions worldwide.